Ruptured Chylous Mesenteric Pseudocyst Mimicking Acute Appendicitis: A Rare Diagnostic Entity - D, Raptis; G, Langas; E, Savvides; T, Pavlidis; N, Voloudakis; E, Kostakis; D, Paikos; I, Moschos; I, Koutelidakis; B, Papaziogas (Archives of Clinical and Medical Case Reports, 2020)
An otherwise healthy 24-year-old female presented to the Emergency Department referring right iliac Fossa and hypogastrium pain, with anorexia. Her clinical, laboratory and radiologic results indicated the possibility of an inflamed appendix. The patient underwent laboratory and ultrasonographic control. The initial diagnosis was acute appendicitis and therefore she was led to the operating theatre, where a typical appendectomy was performed. The patient was asymptomatic, but a great amount of a milk-like fluid was drained through the drainage tube. CT imaging was decided and revealed a mesenteric cyst, which was resected via a midline incision.